2017
DOI: 10.1093/glycob/cwx070
|View full text |Cite
|
Sign up to set email alerts
|

Heparosan-coated liposomes for drug delivery

Abstract: Liposomal encapsulation is a useful drug delivery strategy for small molecules, especially chemotherapeutic agents such as doxorubicin. Doxil® is a doxorubicin-containing liposome ("dox-liposome") that passively targets drug to tumors while reducing side effects caused by free drug permeating and poisoning healthy tissues. Polyethylene glycol (PEG) is the hydrophilic coating of Doxil® that protects the formulation from triggering the mononuclear phagocyte system (MPS). Evading the MPS prolongs dox-liposome cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…In addition, a variety of materials can be used as gene carriers for intracellular delivery of miRNAs (Gessler Dominic et al, 2019). For instance, liposome capsules, drug molecules with phospholipid bilayer vesicles, possess better biocompatibility and stability, which easily get into the cell through endocytosis and achieve gene delivery (Lane Rachel et al, 2017). Moreover, multiple nanosystems, such as organic/inorganic nanoparticles and polymer nanoparticles, have been introduced as functional nanocarriers to complete targeted and intelligent gene delivery by virtue of the physicochemical properties of different materials (Mao et al, 2019).…”
Section: Mirna-based Therapeutic Targetsmentioning
confidence: 99%
“…In addition, a variety of materials can be used as gene carriers for intracellular delivery of miRNAs (Gessler Dominic et al, 2019). For instance, liposome capsules, drug molecules with phospholipid bilayer vesicles, possess better biocompatibility and stability, which easily get into the cell through endocytosis and achieve gene delivery (Lane Rachel et al, 2017). Moreover, multiple nanosystems, such as organic/inorganic nanoparticles and polymer nanoparticles, have been introduced as functional nanocarriers to complete targeted and intelligent gene delivery by virtue of the physicochemical properties of different materials (Mao et al, 2019).…”
Section: Mirna-based Therapeutic Targetsmentioning
confidence: 99%
“…These findings strongly suggest that the ENG-Apt/mIP-10-LP nanocapsules can specifically recognize tumor endothelial cell surface receptors for targeted delivery and subsequent induction of IP-10 protein expression in tumor-bearing mice. Some studies have indicated that certain size of liposome (20-200 nm) could be easier to accumulate into tumors rather than healthy tissues through the enhanced permeability and retention effect (EPR) 37, 38. In our study, the size of ENG-Apt/mIP-10-LP nanocapsules was measured 145 nm, suggesting a possible exist of EPR mechanism.…”
Section: Discussionmentioning
confidence: 47%
“…Using homogenous synthetic heparin polymers, we have found that the heparin polymer needs to be sulfated for binding with Stabilin-1 or Stabilin-2. The nonsulfated polymer, heparosan, does not interact with the Stabilin clearance receptors and may be a good candidate as a vehicle for drug delivery [63,64]. The minimal binding requirement is for the polymer to be at least 10 sugars long and the presence of the 3- O sulfate increases binding affinity at least fivefold [53].…”
Section: Heparin Clearance By Stabilin-1 and Stabilin-2mentioning
confidence: 99%